Peran Perempuan Dalam Pemutusan Mata Rantai Covid-19 Melalui Gerakan Pembagian 1 Juta Masker - ABDULLAH, VERA IRIANI (Jurnal Ilmiah Abdi Mas TPB Unram, 2021)
The first COVID-19 disease on the move was identified in Wuhan, spreading so rapidly that it has an impact on mortality, morbidity, mental health conditions and economic losses. The Indonesian government declared the 2019 corona virus disease a national disaster on March 2, 2020, which poses a big risk to the economic sector. The economic situation of the community increases. So that it will affect the purchasing power of the community including the purchase of PPE (Personal Protective Equipment), namely masks. The use of masks for crew members in the community, where in early January 2020 WHO had not used masks en masse for healthy individuals. However, based on the results of research that has been carried out during the pandemic period, it shows that using a mask is very effective in preventing the transmission of Covid-19. The activity method uses the ball pick-up method where the team goes down directly to the predetermined location of the activity. The results of the distribution of 200 cloth masks can be distributed to targets at 4 locations. The cloth masks brought in this activity are masks with 3 layers consisting of an absorbent on the inside, a layer of non-woven material in the middle such as polypropylene and a non-absorbent material on the outside. So that this cloth mask meets the mask standards requested by WHO, so at least it doesn't use a scuba and buff type mask or doesn't even use it at all.Â